2018
DOI: 10.2500/ajra.2018.32.4485
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Nasolabial Angle according to the Degree of Upper Lip Protrusion in an Asian Population

Abstract: Background The positioning of the nasal tip is as esthetically important as the tip projection when rhinoplasty is being considered. It is not uncommon for Asians to have a protruding upper lip and teeth that affect the nasolabial angle (NLA). This study aimed to find the preferred NLA according to the degree of upper lip protrusion in an Asian population. Methods A left-side lateral photograph of each participant was used for simulation of six different tip angles by using a photoshop program. First, the angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…After subgroup analysis, we further demonstrated that the post-treatment decrease in CLA was statistically significant only in Group B but not in Group A at both 4-week and 12-week follow-ups. CLA or NLA with the best esthetics generally shows a relatively wide range when the degree of upper lip protrusion is small [ 20 ]. However, when lip protrusion is marked, the aesthetically preferred CLA tends to fall within a narrow range, with a strong preference for more acute CLA related to the degree of upper lip protrusion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After subgroup analysis, we further demonstrated that the post-treatment decrease in CLA was statistically significant only in Group B but not in Group A at both 4-week and 12-week follow-ups. CLA or NLA with the best esthetics generally shows a relatively wide range when the degree of upper lip protrusion is small [ 20 ]. However, when lip protrusion is marked, the aesthetically preferred CLA tends to fall within a narrow range, with a strong preference for more acute CLA related to the degree of upper lip protrusion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLA or NLA with the best esthetics generally shows a relatively wide range when the degree of upper lip protrusion is small [ 20 ]. However, when lip protrusion is marked, the aesthetically preferred CLA tends to fall within a narrow range, with a strong preference for more acute CLA related to the degree of upper lip protrusion [ 20 ]. Considering that surgical lip lift results in a significant decrease in the angle of the nasolabial region [ 21 ], a decrease in CLA found in our study implies the lip lifting effect of HA filler injections.…”
Section: Discussionmentioning
confidence: 99%
“…Asian noses are generally more rotated compared with Caucasian noses, with a more obtuse nasolabial angle. 4,5,8 This may lead to the appearance of an "upturned nose" as well as a shorter nasal dorsum-features that are not considered aesthetically pleasing in the Asian context. Consequently, decreasing the rotation of the nasal tip is an important aspect of Asian rhinoplasty.…”
Section: Nasal Tipmentioning
confidence: 99%
“…In such cases, most Asian patients prefer a less acute nasolabial angle after correction instead of the Caucasian ideal of 90 degrees for men and 95 to 105 degrees for women. 8 Premaxillary augmentation is also a consideration in patients with premaxillary deficit. 9…”
Section: Nasal Tipmentioning
confidence: 99%
See 1 more Smart Citation